THE FUTURE UNIVERSITY PROFESSOR'S BUSINESS REPUTATION AS A SCIENTIFIC PHENOMENON - Yunyk, O. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
The existing interpretations of the concept "business reputation of the individual", developed by researchers in various fields of science: marketing, management, accounting and auditing, law, political science, sociology, psychology, military pedagogy, etc. are considered. The following types of person's business reputation are singled out, in particular: professional, financial, legal, administrative, social (personal), etc. It is emphasized that there is a misconception about the synonymy of the terms "business person" and "entrepreneur", associated with the stereotypical perception of both terms as those that characterize a person engaged in entrepreneurship and business. It is noted that the assessment of the business reputation of individual in any field of professional activity (both civilian and military), which provided by representatives of both one and different target audiences, has some differences. Emphasis is placed on the inadequacy of consideration of business reputation in pedagogical science, which is represented by a limited number of works of scientists. The public opinion about the personality of the university professor within the limits of its positive and negative perception is characterized. The unconsidered elements of the business reputation of the future university professor are revealed. The specifics of identifying the modality of their business reputation, which is manifested in the possibility of distinguishing not only the positive characteristics of its carrier, but also negative and neutral (zero) is justified. The specifics of the target audience's perception of the bearer of business reputation, which occurs due to the separation of dominant qualities in his behavior and unconscious comparison of their number and weight, are described. It is proved that the dominance of the bearer of business reputation of positive qualities over negative ones shows the positive modality of the specified phenomenon, in case of predominance of negative qualities over positive ones – negative. The existence of zero business reputation of the future university professor is possible only if the target audience is insufficiently informed about the behavior and personal qualities of its bearer.
Keywords: future university professor, business reputation, positive reputation, negative reputation, zero reputation, structure of business reputation